2017
DOI: 10.1016/j.jare.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed magnetic field versus ultrasound in the treatment of postnatal carpal tunnel syndrome: A randomized controlled trial in the women of an Egyptian population

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
2
12
1
3
Order By: Relevance
“…The research found that these workouts prevent adhesion formation even while the wrist is immobilized, reduce pressure in the carpal tunnel, and increase the relative excursion of the median nerve and flexor tendons. These advantages were found to be consistent with the findings of the current investigation [45].…”
Section: Discussionsupporting
confidence: 91%
“…The research found that these workouts prevent adhesion formation even while the wrist is immobilized, reduce pressure in the carpal tunnel, and increase the relative excursion of the median nerve and flexor tendons. These advantages were found to be consistent with the findings of the current investigation [45].…”
Section: Discussionsupporting
confidence: 91%
“…Static EMF possesses no auxiliary electric fields and cannot transport magnetic power to the movable energized particles 21 ) , designating the efficiency of that type of therapy and describing the deficiency of strong medical sign in the systematic research to encourage its application. PEMF is a broad approach employed in the treatment of various medical dysfunctions, such as musculoskeletal disorders 22 ) , neurological manifestations 23 , 24 ) , and urological disciplines 25 ) . The mechanism of the beneficial performance of the PEMF upon living organisms is not completely obvious yet; however, clinical studies have reported its convenient role in decreasing inflammation, forming new blood vessels, and relieving pain 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…There are quite many studies published lately on the effect of pulsed magnetic field (PEMF) on various diseases such as carpal tunnel syndrome [53], rotator cuff disease [54], and knee osteoarthritis [55]. PEMF has also been used to stimulate bone healing for non-union fractures.…”
Section: Electromagnetic Fields In Health Carementioning
confidence: 99%